Faktor Penghambat Adopsi Mobile Banking Pada Generasi Milenial - Rika Umbaiyani Ritonga, Muhammad Irwan Padli Nasution, Sri Suci Ayu Sundari (Islamic Education Journal, 2023)
The modern world is driven by a direct and simple lifestyle. This is reflected in the development of digital information technology so that information can be managed in real time without human intervention with the help of an automated and sophisticated system. In this case, M-Bank will help you get banking information and services quickly and easily. M-Bank users in the millennial generation, where 4 fields are classified as low. Therefore, this study aims to analyze the obstacles that prevent the millennial generation from adopting M-Bank by applying the Innovation Resistance Theory (IRT). This study uses a quantitative method by filling out an online questionnaire with 155 millennial respondents in m,an 4 to empirically test the innovation sustainability model. The results showed that of the six barriers studied, value barriers, traditional barriers, and image barriers had a negative effect on adoption intentions. Applying an under-researched perspective through innovation resistance theory, this paper helps banks better understand consumer behavior and perceptions, and assists banks in designing solutions to increase m-banking adoption.